Planting Date and Varietal Impact on Growth and Yield of Potato - Kawar, Aakriti; Sharma, Raksha; Regmi, Bishma Raj; Ghimire, Nabin (Genetics, Plant Breeding and Seed Science, 2025)
Identification of suitable planting dates for improved agricultural yield is challenging due to climate change. An experiment was conducted in Damada, Dadeldhura, to evaluate the performance of potato varieties at various planting dates. The study was conducted in a factorial randomized complete block design where four varieties: MS-42.3, Khumal Seto-1, Cardinal, and, Desiree were in factor A and three planting dates (10th February, 20th February, and 1st March) were in factor B; altogether 12 treatments were replicated thrice. The analysis of variance revealed significant variations in the yield among the varieties, planting dates, and their interactions. Among the varieties, Desiree took the longest time (24 days) for emergence, while Khumal Seto-1 emerged early (21 days) on all planting dates. The plant height, number of branches, and leaves were significantly higher for Khumal Seto-1 when planted on 1st March. Among the varieties, the highest yield was recorded in Khumal Seto-1 with 46.32 t/ha, when planted on 20th Feb, followed by MS-42.3 (38.15 t/ha) planted on 1st March. The lowest yield was recorded in Desiree (17.05 t/ha) when planted on 1st March. However, Khumal Seto-1, Cardinal, and Desiree produced higher yields on 20th Feb except for MS-42.3, which produced higher yields on 1st March. The results showed significant differences in total tuber number, average weight, and yield of potato tubers at different planting dates and varieties. Among the three planting dates, Khumal Seto-1 yielded the highest average production (40.84 t/ha), with a peak yield (46.32 t/ha) observed when planted on 20 February. Although this clone achieved the highest overall yield, its performance was significantly influenced by planting date, with lower yields when planted too early or late. This highlights the critical role of both varietal selection and optimal planting timing in improving food security in Dadeldhura’s hilly agroecology.